Hubungan Antara Obesitas dengan Kejadian Anemia pada Balita Usia 3-5 Tahun di Desa Payabedi Kec. Rantau, Kab. Aceh Tamiang - Leli Mitra Niat Laia; Khoiri Amni Siregar; Kiki Purnama Sanjani Sitanggang; Lailatul Ikmah Marpaung; Debi Novita Siregar (Malahayati Nursing Journal, 2023)
ABSTRACT One of the main problems of the Government of Indonesia for children under five is overweight or obesity, which has a risk of anemia in children under five. Obesity is the biggest global public health challenge as the top three causes of chronic health disorders. The incidence of obesity in toddlers has an impact on children's growth and development and is related to the occurrence of systemic inflammation that causes iron deficiency resulting in anemia. Anemia is a decrease in red blood cells (hemoglobin) and if not treated for a long time in toddlers it can cause growth and development problems, and disrupt the immune system so that they are susceptible to infectious diseases. Thexpurpose ofxthis studyxwas toxdetermine the relationship between obesityxand thexincidence ofxanemia in children aged 3-5 years in Payabedi Village, Rantau District, Aceh Tamiang Regency in 2022. The typexof researchxused was anxobservationalxstudyxwith a correlational design. The results of the chi-square test obtained a p-value of 0.652 (pα (0.05), so Ho is accepted. The conclusion based on statistical analysis proves that therexis noxrelationshipxbetween obesityxand thexincidence of anemia in toddlers aged 3-5 years in PayabedixVillage, Kec. Rantau, Aceh Tamiang District in 2022. The results of this study are expected to be used by the Payabedi Village Leaders and Staff, Rantau District, Aceh Tamiang District to plan a program to improve the population's nutrition, especially for children. Keywords : Obesity, Anemia, Toddler.  ABSTRAK Salah satu masalah utama Pemerintah Indonesia untuk anak balita adalah kegemukan atau obesitas, yang yang memiliki risiko anemia pada balita. Obesitas suatu tantangan terbesar kesehatan masyarakat global sebagai peringkat tiga besar penyebab gangguan kesehatan kronis. Kejadian obesitas pada balita berdampak terhadap tumbuh kembang anak dan berhubungan dengan terjadinya inflamasi sistemik yang menyebabkan defisiensi zat besi berakibat terjadinya anemia. Anemia ialah berkurangnya sel darah merah (hemoglobin) dan apabila tidak ditangani dalam waktu lama pada balita dapat menimbulkan masalah pertumbuhan dan perkembangan, sertaxmengganggu sistemximun sehinggaxmudah terserangxpenyakit infeksi. Tujuan penelitian ini untuk mengetahui hubungan antara obesitas dengan kejadian anemia pada balita usia 3-5 tahun di Desa Payabedi Kec. Rantau, Kab. Aceh Tamiang tahun 2022. Jenisxpenelitian yang digunakanxialah penelitian observasional dengan desain korelasional. Hasil uji chi-square diperoleh nilai p-value 0,652 (pα (0,05), sehingga Ho diterima. Kesimpulannya berdasarkan analisis statistik membuktikan tidak terdapat hubungan antara obesitas dengan kejadian anemia pada balita usia 3-5 Tahun di Desa Payabedi Kec. Rantau, Kab. Aceh Tamiang Tahun 2022. Hasil penelitian ini diharapkan dapat dimanfaatkan Pimpinan dan Staf Desa Payabedi Kec. Rantau, Kab. Aceh Tamiang untuk merencanakan program perbaikan gizi penduduk terlebih pada anak-anak. Kata Kunci: Obesitas, Anemia, Balita.